Reflections on divorce in Bessarabia in the first half of the nineteenth century: the adultery - Alina Felea (Codrul Cosminului, 2012)
The article covers a topic related to family history - divorce, insufficiently treated in historiography. In this study based on concrete examples from Bessarabia, it will be presented the daily reality in the problem of divorce granted for adultery and how the canons of the church were respected in the first half of the nineteenth century. As sources of research were used documents from the funds of the State Archives of Republic of Moldova, showing the fact of initiation of divorce processes by representatives of different social classes: nobles, townspeople, peasants, soldiers etc.